- Integrasi Video Microlearning dan Gamification dalam Pembelajaran Leadership Mahasiswa Kedokteran: A Pre Experimental Study: Indonesia - Jesica Mulyadi; Zuhriana K. Yusuf; Riska Nuryana; Sulaiman Putra Nagaring; Sitty Fadhilla Fitrianty Lahay (Faculty of Health Sciences , Dr. Soetomo University, 2026)
Abstract Background: Digital transformation in medical education has encouraged the implementation of innovative learning methods that are more interactive and student-centered. The integration of video microlearning and gamification is considered capable of improving the effectiveness of leadership learning among medical students through a more flexible, engaging, and participatory learning experience. This study aimed to analyze the effect of integrating video microlearning and gamification on leadership knowledge among medical students. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The study was conducted among fourth-semester undergraduate medical students with a total sample of 65 respondents selected using total sampling technique. The intervention consisted of short-duration microlearning videos on transformational leadership theory followed by gamification-based interactive quizzes using the Quizizz platform. Leadership knowledge was measured using a 16-item multiple-choice questionnaire that had been validated (p<0.001) and demonstrated good reliability (Cronbach’s Alpha=0.78). Data were analyzed using a paired t-test with a significance level of p<0.001. Results: Most respondents were female (72%). The findings demonstrated an increase in the mean leadership knowledge score following the intervention. The mean pretest score increased from 9.46 to 15.28 in the posttest, with a mean difference of 5.82. Statistical analysis revealed that the integration of video microlearning and gamification had a significant effect on improving leadership knowledge among medical students (p<0.001). Conclusion: The integration of video microlearning and gamification was effective in improving leadership knowledge among medical students. This technology-based learning approach has the potential to become an innovative strategy for promoting more active, interactive, and student-centered leadership learning in medical education.